Rural secondary school teachers' capacity to respond to HIV and AIDS: the case of Shurugwi district in Zimbabwe. - Mangwaya, Ezron; Ndlovu, Emily (2016)
Young people often turn to their teachers for information on sexuality and HIV and Aids. Consequently, need to be not only knowledgeable about these issues but also able to integrate them into their teaching of an umbrella study to investigate and promote HIV and AIDS education and support in schools, this reports on a qualitative study conducted among a purposively selected sample of teachers in Shurugwi ascertain their response to the challenges resulting from the pandemic. The findings suggest that the participating teachers held complex and contradictory views about HIV and Aids education; that they were constrained by to, prevailing social and cultural background; and that their responses were inhibited by the lack of adequate social welfare support systems. These factors combined to make it difficult for them to interpret and implement policy that calls for a coherent and collaborative response. This study will hopefully inform professional development, interventions to ensure that future HIV and AIDS teaching and learning s relevant and effective, given the social and educational context.